Adopting “Results-based management policy innovation : a tool for strategy planning and execution” : a case study of the United Nations human settlements programme - Olupot, Geoffrey (Stellenbosch : Stellenbosch University, 2016)
Thesis (PhD)--Stellenbosch University, 2016.